The Effect of Adversity Quotient and Locus of Control on Entrepreneurial Intentions on Universitas Mulawarman Students - Ramadani, Desita Putri; Haidar, Kadori; Rahayu, Vitria Puri; Ellyawati, Noor (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2023)
There are 3 research objectives to determine whether adversity quotient affects entrepreneurial intentions, whether the locus of control affects entrepreneurial intentions, and whether adversity quotient and locus of control affect entrepreneurial intentions in Universitas Mulawarman students majoring in Economics Education. This study utilizes a quantitative method combined with descriptive research. Multiple regression analysis is used for data analysis. The findings indicate that adversity quotient and locus of control influence entrepreneurial intentions, as seen in the student's tendencies to act upon said intentions, such as attending seminars and doing research on the topics of entrepreneurship. This tendency to act arises when students don't let the difficult situation affect them too much because of their belief in their ability to control their situation, which often means that these students have higher confidence in their business pursuits. This shows that adversity quotient and locus of control can be seen in the sense of worth and the ability to identify the source of the financial problems that these students possess, even though they are often hampered by limited resources.